Improved platinum‐nickel nanoparticles with dopamine‐derived carbon shells for proton exchange membrane fuel cells. (13th May 2022) - Jang, Injoon; Lee, Sehyun; Jang, Jue‐Hyuk; Ahn, Minjeh; Yoo, Sung Jong
Summary: Using platinum‐based alloy nanocatalysts with other transition metals has the advantages of enhancing the oxygen reduction reaction (ORR) activity and reducing the platinum usage. However, there are many challenges to using nanocatalysts, including their instability, which hinder their practical application. In this study, we employed a strategy to improve the intrinsic instability of a nanocatalyst by encapsulating a dopamine‐derived carbon layer on the surfaces of nanoparticles. The carbon layer formed on the surfaces of platinum‐nickel (PtNi) nanoparticles demonstrated improved stability by inhibiting the nanoparticle growth, even during the heat treatment process. This could induce a high degree of alloying while minimizing the loss of surface area for the nanoparticles, which ensured an improved catalyst activity. Additionally, the PtNi nanocatalyst with the dopamine‐derived carbon layer showed an improved performance and stability under long‐term fuel cell operation conditions, thus proving the practicality of this strategy. The strategy developed in this study is not only a novel and facile approach to the synthesis of alloy catalysts, but also addresses the inherent instability of nanoparticles, which will encourage the practical use and commercialization of alloy nanocatalysts. Abstract : Using platinum‐based alloy nanocatalysts with other transition metals has the advantages of enhancing the oxygen reduction reaction (ORR) activity and reducing the platinum usage. However, there are many challenges to using nanocatalysts, including their instability, which hinder their practical application. In this study, we employed a strategy to improve the intrinsic instability of a nanocatalyst by encapsulating a dopamine‐derived carbon layer on the surfaces of nanoparticles.